Enhanced photovoltaics inspired by the fovea centralis - Shalev, Gil; Schmitt, Sebastian W.; Embrechts, Heidemarie; Broenstrup, Gerald; Christiansen, Silke (Scientific Reports, 2015)
The fovea centralis is a closely-packed vertical array of inverted-cone photoreceptor cells located in the retina that is responsible for high acuity binocular vision. The cones are operational in well-lit environments and are responsible for trapping the impinging illumination. We present the vertical light-funnel silicon array as a light-trapping technique for photovoltaic applications that is bio-inspired by the properties of the fovea centralis. We use opto-electronic simulations to evaluate the performance of light-funnel solar cell arrays. Light-funnel arrays present ∼65% absorption enhancement compared to a silicon film of identical thickness and exhibit power conversion efficiencies that are 60% higher than those of optimized nanowire arrays of the same thickness although nanowire arrays consist of more than 2.3 times the amount of silicon. We demonstrate the superior absorption of the light-funnel arrays as compared with recent advancements in the field. Fabrication of silicon light-funnel arrays using low-cost processing techniques is demonstrated.
CRIS-Team Scopus Importer:2023-03-07